THE SPECIFIC FEATURES OF ENSURING THE ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES - Uktamov Khusniddin (Scholar Express Journals, 2024)
In today's global economic environment, most companies operate in conditions of uncertainty, unpredictability. The unstable political and socio-economic situation in the country increases the degree of risk of decision-making and the functioning of enterprises in general. In such conditions the problem of ensuring the economic security of the enterprise becomes relevant. This determines the relevance of studying the issue of economic security of enterprises in modern conditions. The structure of the functional components of economic security of the enterprise consists of: financial, political and legal, technical and technological, information, personnel, environmental, commercial, power and intellectual.
Keywords: economic security; small business; systematic analysis; business entities